Outcome of Selective Laser Trabeculoplasty in Young Patients with Primary Open-Angle Glaucoma and Ocular Hypertension - Dan Liu; Di Chen; Qian Tan; Xiaobo Xia; Haibo Jiang; Jian Jiang (Journal of Ophthalmology)
Purpose. To determine the effectiveness and safety of selective laser trabeculoplasty (SLT) in young patients with primary open-angle glaucoma (POAG) and ocular hypertension (OHT). Methods. This was a retrospective clinical study. Fifty-six eyes from 56 young (age ≤ 40 y) patients with POAG or OHT treated with SLT were included. According to age, patients were divided into group 1 and group 2. Patients in group 1 were younger than 18 years old, and patients in group 2 were between 18 and 40 years old. Patients were evaluated before treatment and at 1 hour, 1 day, 1 week, 1 month, 3 months, 6 months, and 1 year after treatment. We also collected older patients (age ≥ 60 y) who received SLT during the same period for comparison at 1-year follow-up. Possible factors affecting the success of SLT, including baseline IOP, age, sex, diagnosis (POAG or OHT), and whether or not use of antiglaucoma medication before treatment, were analyzed. Results. SLT treatment produced significant reduction in IOP in the young patients with POAG or OHT during the 1-year follow-up period（P<0.05）. Mean IOP at 1 hour after SLT was lower in group 1 than in group 2 (P<0.01), but at other follow-up time points, IOP values were not different (P>0.05). IOP reduction and success rate were not significantly different between young and old patients at 1 year after treatment. IOP measurements over a 24-hour period were recorded before and after the SLT in 20 young adult patients. IOP values were significantly lower in the treated patients at all time points than at pretreatment (P<0.05), and 24-hour mean IOP, peak IOP, valley IOP, and fluctuation in IOP were also lower in SLT-treated patients (P<0.05). Baseline IOP was found as a predictor of SLT success in young patients (OR = 1.895, P=0.003), whereas age, gender, diagnosis, and whether or not use of antiglaucoma medication were not correlated with SLT success (P=0.725, P=0.750, P=0.061, and P=0.201, respectively). Conclusion. In this study, SLT was found as an effective and safe treatment for young patients with POAG and OHT. High baseline IOP predicted high SLT success.